The association between nitroglycerin use and adverse outcomes in women undergoing cesarean delivery in the second stage of labor. (3rd June 2017) - Isquick, Sarah; Henry, Dana; Nakagawa, Sanae; Moghadassi, Michelle; Thiet, Mari-Paule; Norton, Mary; Lucero, Jennifer
Abstract: Objective : To identify predictors of hysterotomy extension in women undergoing cesarean delivery (CD) in the second stage of labor, and whether use of nitroglycerin (NTG) during CD has a protective effect. Methods : We conducted a retrospective cohort study of women undergoing CD in the second stage of labor from 2012 to 2015. Some women received NTG at the obstetrician's request. Logistic regression was used to examine the relationship between second stage duration and NTG administration on maternal and neonatal outcomes. Results : Of the 391 women in the sample, 27% had an extension and 12% received NTG. Second stage ≥4 h was associated with a 2.14-fold higher risk of extension (95% CI 1.22–3.75), a 2.00-fold higher risk of hemorrhage (95% CI: 1.20–3.33) and 2.42-fold higher risk of blood transfusion during delivery hospitalization (95% CI: 0.99–5.91). Intravenous (IV) and sublingual-spray (SL-spray) NTG administration were not associated with an increased risk of hemorrhage or extension. SL-NTG was associated with 4.68-fold increased odds of 5-min Apgar <7 (95% CI 1.42–15.41) and 3.36-fold greater odds of NICU admission (95% CI 1.20–9.41). Conclusion : We found no evidence that NTG protects against extension, and SL-NTG use was associated with adverse neonatal outcomes. Clinical trials should be conducted to evaluate risk and benefits of NTG use.